Multipotent Neural Crest Stem Cell-Like Cells from Rat Vibrissa Dermal Papilla Induce Neuronal Differentiation of PC12 Cells. (18th June 2014) - Li, Meiying; Liu, Jin Yu; Wang, Shichao; Xu, Hao; Cui, Lifeng; Lv, Shuang; Xu, Jinying; Liu, Shutong; Chi, Guangfan; Li, Yulin
Abstract : Bone marrow mesenchymal stem cells (BMSCs) transplants have been approved for treating central nervous system (CNS) injuries and diseases; however, their clinical applications are limited. Here, we model the therapeutic potential of dermal papilla cells (DPCs) in vitro . DPCs were isolated from rat vibrissae and characterized by immunocytofluorescence, RT-PCR, and multidifferentiation assays. We examined whether these cells could secrete neurotrophic factors (NTFs) by using cocultures of rat pheochromocytoma cells (PC12) with conditioned medium and ELISA assay. DPCs expressed Sox10, P75, Nestin, Sox9, and differentiated into adipocytes, osteoblasts, smooth muscle cells, and neurons under specific inducing conditions. The DPC-conditioned medium (DPC-CM) induced neuronal differentiation of PC12 cells and promoted neurite outgrowth. Results of ELISA assay showed that compared to BMSCs, DPCs secreted more brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF). Moreover, we observed that, compared with the total DPC population, sphere-forming DPCs expressed higher levels of Nestin and P75 and secreted greater amounts of GDNF. The DPCs from craniofacial hair follicle papilla may be a new and promising source for treating CNS injuries and diseases.